High‐energy collision‐induced dissociation of histidine ions [His + H]+ and [His − H]− and histidine dimer [His2 + H]+. (21st December 2017) - Khreis, Jusuf M.; Reitshammer, Julia; Vizcaino, Violaine; Klawitter, Kevin; Feketeová, Linda; Denifl, Stephan
Abstract : Rationale: Histidine (His) is an essential amino acid, whose side group consists of an aromatic imidazole moiety that can bind a proton or metal cation and act as a donor in intermolecular interactions in many biological processes. While the dissociation of His monomer ions is well known, information on the kinetic energy released in the dissociation is missing. Methods: Using a new home‐built electrospray ionization (ESI) source adapted to a double‐focusing mass spectrometer of BE geometry, we investigated the fragmentation reactions of protonated and deprotonated His, [His + H] + and [His − H] −, and the protonated His dimer [His2  + H] +, accelerated to 6 keV in a high‐energy collision with helium gas. We evaluated the kinetic energy release (KER) for the observed dissociation channels. Results: ESI of His solution in positive mode led to the formation of His clusters [His n + H] +, n = 1–6, with notably enhanced stability of the tetramer. [His + H] + dissociates predominantly by loss of (H2 O + CO) with a KER of 278 meV, while the dominant dissociation channel of [His − H] − involves loss of NH3 with a high KER of 769 meV. Dissociation of [His2 + H] + is dominated by loss of the monomer but smaller losses are also observed. Conclusions: The KER for HCOOH loss from both [His + H] + and [His − H] − is similar at 278 and 249 meV, respectively, which suggests that the collision‐induced dissociation takes place via a similar mechanism. The loss of COOH and C2 H5 NO2 from the dimer suggests that the dimer of His binds through a shared proton between the imidazole moieties.